Compactness in quasi-Banach function spaces and applications to compact embeddings of Besov-type spaces - Caetano, António (2018)
There are two main aims of the paper. The first one is to extend the criterion for the precompactness of sets in Banach function spaces to the setting of quasi-Banach function spaces. The second one is to extend the criterion for the precompactness of sets in the Lebesgue spaces $L_p(\Rn)$, $1 ≤ p < ∞$, to the so-called power quasi-Banach function spaces. These criteria are applied to establish compact embeddings of abstract Besov spaces into quasi-Banach function spaces. The results are illustrated on embeddings of Besov spaces $B^s_{p,q}(\Rn)$, $0<s<1$, $0<p,q≤ ∞$, into Lorentz-type spaces.